Rebooting education: Leadership and professionalism of vocational school teachers in the era of socio-cultural transformation - Adi Kusumardi; Farida Hanum; Serafin Wisni Septiarti; Dirman Hanafi (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2026)
The rapid expansion of digital technology is reshaping social and cultural values, fundamentally altering how individuals learn, work, and interact. This transformation compels vocational education to undergo substantive restructuring beyond mere technological adoption. This study investigates how vocational secondary school (SMK) teachers reconstruct learning leadership practices, reinterpret teacher professionalism, and integrate local wisdom in response to curriculum reform, digital disruption, and socio-cultural transformation within the Indonesian context. Drawing on Interpretative Phenomenological Analysis (IPA), this research engaged twelve purposively selected vocational school teachers across urban, semi-urban, and rural settings in the Bangka Belitung Islands as primary participants. Data were generated through in-depth interviews, classroom observations, and document analysis and subjected to thematic coding using the IPA protocol. Findings reveal three interdependent dimensions: (1) contextual instructional leadership that shifts from administrative to adaptive-reflective modes; (2) digital-cultural professionalism that integrates technological literacy with indigenous values; and (3) a locally-grounded Teaching Factory (TeFa) ecosystem that negotiates between industrial standards and community identity. These dimensions constitute the Rebooting Education conceptual model, which extends instructional leadership theory (Hallinger, 2020), expands TPACK toward digital-cultural integration (Mishra & Koehler, 2006), and operationalises glocalisation in vocational practice (Robertson, 2020). The study contributes a theoretically-grounded framework for policy and teacher professional development in contexts where global educational pressures intersect with strong local cultural systems.